Slope Stability Analysis at Pit 1 Limestone Mining PT Anugrah Halaban Sepakat, Lareh Sago Halaban Sub-District, Lima Puluh Kota Regency, West Sumatra Province - Juni Pratama; Raimon Kopa (Departemen Teknik Pertambangan FT UNP, 2022)
PT Anugrah Halaban Sepakat is one of the companies engaged in the mining sector and has invested in Fifty Cities Regency, West Sumatra Province. PT Anugrah Halaban Sepakat has two pits (pit 1 and pit 2), the slope characteristics of pit 1 are composed of homogeneous clay material which tends to be sticky in wet conditions, hard and cracked in dry conditions, has a geometry of 20 meters high. and a slope of 66°, which was made without taking geotechnical studies into account. Based on this, it is necessary to plan the research slope well so that the soil slope is in a stable condition. From the results of research and analysis carried out, the value of geotechnical parameters after testing the physical and mechanical properties of the slope material is the natural density of 15,77 kN/m3, the dry density of 14,14 kN/m3, and the saturated weight of 19,06 kN/m3. The cohesion value is 39,79 kN/m3, and the internal shear angle is 21,25°. The actual FK value in natural state using Bishop's method is 1,099, in dry state is 1,177 and saturated state is 0,985. Then the actual FK value using the Hoek and Bray method in dry conditions was obtained at 1,051 and in a saturated state of 0,720. The results of the analysis after modifying the single slope geometry from a slope of 66o to 46o, the FK value in the dry state is 1,562 and the saturated state is 1,319 by dismantling the soil as much as 4.262,076 m3. Then the results of the analysis after modifying the geometry of the overall slope made two single slopes each with a height of 7 and 13 meters and a bench width of 10 meters having a slope of 50o, the FK value in a dry state was 1,550 and in a saturated state of 1,315 by dismantling 2.514,35 m3 of soil.